Exposure to Per- and Polyfluoroalkyl Substances (PFASs) in Healthcare: Environmental and Clinical Insights - George Briassoulis; Stavroula Ilia; Efrossini Briassouli (Life)
Per- and polyfluoroalkyl substances (PFASs) are synthetic chemicals extensively used in various industries due to their unique physicochemical properties. Their persistence in the environment and potential for bioaccumulation have raised significant health concerns. This review aims to elucidate the sources, exposure pathways, toxicological effects, and regulatory measures related to PFASs, with a particular focus on pediatric populations and medical applications. A comprehensive narrative review was conducted using PubMed, Scopus, and Web of Science to identify peer-reviewed literature published between 2000 and 2025. The search focused on PFAS use in healthcare, environmental contamination, exposure pathways, health effects, and regulatory actions. Relevant studies, reports, and policy documents were screened and thematically synthesized by the authors to evaluate clinical and environmental risks, particularly in pediatric populations. PFAS exposure is linked to various adverse health effects, including immunotoxicity, endocrine disruption, metabolic disorders, and carcinogenicity. Children are particularly vulnerable due to developmental susceptibilities and exposure through medical devices and environmental sources. Regulatory measures are evolving, but gaps remain, especially concerning medical device applications. There is an urgent need for comprehensive strategies to monitor and mitigate PFAS exposure, particularly in vulnerable populations. Enhanced regulatory frameworks, safer alternatives in medical devices, and public health interventions are essential to address the challenges posed by PFASs.